基于稳态流体模型的齿轮箱强制润滑系统研究 - 靳国忠; 张亚楠; 徐佳宁 (Jixie chuandong)
Because of forced lubrication system plays a significant role in the design life of the gearbox,traditional rough estimate and ordinary design can not meet the product requirements of working conditions.A design method for gearbox forced lubrication system based on steady fluid model,making full use of the fluid simulation technology progress is explained.This method,through test verification experimental and practice verification,it is proved to be effective for the lubricating and cooling,and it will conducive to long-term stable operation of the gearbox.